ACUTE EFFECTS OF THE INTENSITY IN THE AGONIST-ANTAGONIST PAIRED-SET ON THE NEUROMUSCULAR PERFORMANCE - Costa, Bruna Daniella de Vasconcelos (2020)
The intensity employed in the agonist-antagonist paired-set (AAPS) system may influence neuromuscular performance due to increased fatigue and decreased antagonist coactivation. However, it is not yet known whether performing submaximal repetitions at different intensities (i.e., without muscle failure) negatively affects agonist muscle performance. The aim of this study was to verify the acute effect of the AAPS system performed at different intensities with submaximal repetitions. 20 trained males in resistance training (RT) (21.8 [3.1] years; 76.9 [9.7] kg; 1.7 [0.0] m; 24.3 [2.6] kg/m2) participated of this investigation. All the participants were allocated in randomized order in one of the two AAPS configurations: High-load (HL) or Low-load (LL). In the HL condition, the individuals were submitted to one set of eight repetitions at 75% of one repetition maximum (1RM) in the knee flexion (i.e., antagonist), followed by 75% 1RM knee extension (i.e., agonist) exercise until momentary concentric failure. In the LL condition, they performed one set of 12 repetitions at 50% 1RM in the knee flexion, followed by knee extension at 75%1RM also until momentary concentric failure. Both experimental conditions presented similar values for the number of repetitions, without significant difference (P = 0.66, ES = 0.15). Thus, our data suggest that the adoption of AAPS system without increase of the antagonist fatigue and consequently no reduction of coactivation, acutely, may not lead to increased performance of target musculature during a resistance exercise session.